Reactive amyloidosis complicated by end-stage renal disease 28 years after liquid silicone injection in the buttocks. (3rd October 2012) - d'Ythurbide, Geraldine; Kerrou, Khaldoun; Brocheriou, Isabelle; Hertig, Alexandre
Abstract : Silicone ganulomas usually arise from the rupture of silicone implants. Until the 1980s, however, underground care providers used to inject liquid and unapproved silicone directly into human tissues, in the absence of a containing capsule. We report here the case of a man who ultimately developed end-stage renal disease (ESRD) because of a chronic glomerulosclerosis that was attributed to a glomerular AA amyloidosis diagnosed 28 years after a buttock injection of liquid silicone. To our knowledge, this is the first case of a silicone-induced AA amyloidosis irreversibly affecting the kidneys, and leading to ESRD. An interleukin 1 receptor antagonist was started to prevent the extension of amyloidosis, but to no avail as far as the kidneys are concerned. We want to draw the attention of health professionals about the risk of developing AA amyloidosis secondary to a long-lasting inflammation induced by silicone leakage, after a long latency period.